Direct preparation of activated carbon fiber aerogel via pyrolysis of cotton under CO2 atmosphere and its adsorption of methylene blue. Issue 9 (2nd May 2020) - Cao, Junrui; Ma, Yuhui
ABSTRACT: A novel activated carbon fiber aerogel (ACFA) was prepared in one step via pyrolysis of cotton under pure CO2 atmosphere. The product was characterized by scanning electron microscope (SEM), N2 -adsorption/desorption, Raman spectroscopy, and Fourier transform infrared spectroscopy (FTIR). The adsorption isotherms and kinetics of methylene blue (MB) by the product were elucidated. The experimental results demonstrated that ACFA had a twisted fibrous structure with a diameter of about 5 μm. The BET surface area and total pore volume of ACFA were up to 734 m 2 g –1 and 0.428 cm 3 g –1, respectively. ACFA had a highly turbostratic graphite structure with many oxygen-containing functional groups on its surface. The adsorption equilibrium data could be represented by Langmuir isotherm model, showing a maximum monolayer adsorption capacity of 204 mg g –1, and the kinetic data followed closely the pseudo-second-order kinetic model. The results proved that cotton could be a promising candidate for the preparation of ACFA with developed porous structure and high adsorption capacity.